ANALISIS PERILAKU KONSUMEN DALAM PROSES PEMBELIAN IKAN HIAS AIR LAUT DI BUNAKEN AKUARIUM KOTA BEKASI - Lutfiadi, Ridwan; Hamzah, Ferdian Mahendra (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2013)
Competition ornamental fish in Bekasi increasingly stringent, requiring appropriate marketing strategies to excel compete. One way that can be taken by employers ornamental fish including Bunaken Aquarium, is a strategy to increase sales volume by studying and knowing the factors that influence consumers decide to buy ornamental fish. The purpose of this study was to determine (1) the consumer characteristics of ornamental fish in Bunaken Aquarium, (2) ornamental fish type whatever demand by consumers, and (3) factors that influence the purchase of ornamental fish in Bunaken Aquarium.The method used in this study is a survey method. The data will be used in this study are primary and secondary data. The sampling technique used was purposive sampling method, with a total sample of 100 respondents. Analysis of the data : (1) descriptive analysis to get an overview of consumer characteristics and type of ornamental fish that consumers demand; (2) factor analysis with factor analysis PCA extraction method. The results showed that the majority of respondents were male (71%), aged 20-30 years (81%), unmarried (73%), family size 3-5 people, educated scholars (49%), private sector employees ( 42%), and the average monthly income of more than Rp. 2,500,000. Ornamental fish species are widely purchased by consumers in the top five is Clown Fish, Blue Stone, Rivet, Beauty and Six Letter / Dori. The factors that influence consumer decisions in the purchase of ornamental fish are cultural factors, social factors, personal factors, and psychological factors.